Medial Plantar Flap for Reconstruction of Heel Defect - Raymond, Benny; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Heel is subjected to exceed weight bearing and shearing forces. Full-thickness defects to the plantar surface of the foot present a challenge. Variety of procedures have been described for resurfacing this site, but not all achieve normal foot function. Reporting two cases, defects of the plantar surface of the heel resurfaced with medial plantar flap, an island fasciocutaneus flap and innervated, thus provide a good replacement.One patient show good result within 4 weeks, with minimal raw surface on secondary defect. While other patient didn’t show up after 2 weeks. Medial plantar flap was successfully used for heel defect reconstruction. Donor site morbidity was minimal, and patient could walk post-operatively without special devices for the heel.